A Survey of Weeds of Wheat Crop Fields in Narwana Region, India (International Journal of Scientific Research and Management (IJSRM), 2017)
The wheat cropping system is very important in India. Also, the weed infestation is a major problem in the productivity of wheat. The present work is based on field research conducted from January, 2017 to March, 2017 in Narwana region of Haryana state, India. Multiple field visits were performed to investigate weed species in wheat crop. The plants were identified with the help of available literature and through comparison with the already identified plant species. Data inventory has been documented in the form of family, Botanical name, vernacular name, life form and habit. Total 54 weed species were collected, related to 50 genera and 22 families. Maximum number of species were of family Poaceae (11species) followed by family Asteraceae (10 species) and Fabaceae (08 species). Out of the 54 weed species, there were 46 annuals and 08 perennials. This study will be helpful as an additional tool in maintaining the floristic composition of Narwana region as well as in controlling the weed problem.